USULAN PERBAIKAN SISTEM PENCAHAYAAN DI UNIT PERCETAKAN PERUSAHAAN XXX SUMATERA UTARA - Poppy Cynthia Devi; A. Rahim Matondang; Dini Wahyuni (Jurnal Teknik Industri USU, 2014)
Lighting as one of workplace environment factor affects the productivity of people. Initial observation at Printing Unit workplace of XXX Company indicated unsuitable lighting for existing jobs. Initial measurement of illumination level on several measurement points showed range from 34,3 lux to 195,4 lux, while standard of illumination level for kind of continuous and rough work listed on Health Minister Regulation No 1405 year 2002 is 200 lux. The impact of bad lighting indications led to a number of reject products passed the inspection session ranged from 2 to 11% per day on initial observation. In this research, illumination level measurement was performed along with observation towards reject products that passed the inspection session. Quantitative method is used on this research. The result shown that the average illumination level of workplace was 41,85 lux and the number of reject products that passed the inspection session reached 5-11% per batch. Changing the type of lamp and also adding a number of lamps were recommended to fulfill the standard of average illumination level. The recommended lamp said to be used is 16 units of energy-saving lamp type Master PL-L 4P80W. Maximum spaces between luminaires are 3,63m.